Facebook Hoax: Etika Berkomunikasi di Media Sosial Analisis QS. Al-Hujurat Ayat 6. - Lia Dwi Utami; Ahmad Abdul Qiso; Ani Nafisah (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2022)
This study aims to offer the use of "Facebook" as an alternative tool to convey news and opinion publications as well as make it easier to meet and interact socially and eliminate the spread of hoax news by referring to QS. Al-Hujurat (49):6. To examine this, in this research, the researcher uses a type of library research (library study), by using primary and secondary sources, and using data analysis techniques that include data reduction, data presentation, and verification. The results of this study are 1) The hoax phenomenon is a very dangerous social problem because hoax news spread on Facebook social media is countless and every day even every second there is always hoax information; and 2) Hoax prevention in the QS facebook application. Al-Hujurat (49): 6 is that Allah SWT gives guidance to us to be careful, not rash and not in a hurry in receiving or delivering news, especially if the news violates several provisions that have been in effect or have been agreed upon such as the provisions of reason. health, good manners and religion. Religious guidance so that we become smarter people in attitude.